Impact of technological innovation on the performance of Chinese listed seed companies: The moderating role of supply chain concentration - Zhang, Ning; Talib, Zunirah Mohd; Ahmad, Muhammad (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of technological innovation on the performance of Chinese seed firms, as well as the moderating effect of supply chain concentration, aiming to provide actionable strategies for seed firms to enhance their sustainable development. Analyzing panel data from Chinese listed seed firms (2013–2022) through lagged regression models, results show that both R&D intensity and patents have a significant negative impact on ROE in the current period, likely due to short-term cost pressures. However, R&D intensity exhibits a significant positive relationship with ROE from a lag of two periods, indicating long-term benefits. Patents show a positive but insignificant relationship from a lag of three periods. Supply chain concentration weakens the negative relationship between R&D intensity and ROE, suggesting that optimizing supply chain concentration can moderate short-term costs and enhance long-term performance. Given the unique industry characteristics of seed companies, strategic supply chain management is crucial for leveraging innovation investments. This study highlights the importance of balancing short-term costs with long-term benefits in driving sustainable competitiveness.